The workers opinions have a value in the Code of Ethics: Analysis of the contributions of workers in virtual Forum Catalan Institute of Health. Issue 1 (December 2015) - Peguero, Eva; Berenguera, Anna; Pujol-Ribera, Enriqueta; Roman, Begoña; Prieto, Carmen; Terribas, Núria
Abstract Background The Catalan Institute of Health (CIH) is the largest health services public provider in Catalonia. "CIH Code of Ethics Virtual Forum" (CEVF), was created within the Intranet of the CIH to facilitate participation among their employees. The current study aims to: a) Analyse the CIH workers' assessment of their own, their colleagues' and the organization's observance of ethical values; b) Identify the opinions, attitudes, experiences and practices related to the ethical values from the discourse of the workers that contributed voluntarily to the CEVF. Methods Mixed methods study withconvergent parallel design :1. Cross sectional study by means of a self-administered, ad hoc, anonymous questionnaire to assess the observance of the ethical values of the CIH according to the participants. A total of 712 workers responded to the questionnaire. A descriptive, bivariate analysis of the results was carried out. 2. Qualitative study to determine the meaning for the workers of the ethical values put forward by the organization. Their individual opinions and experiences were explored by means of a thematic contents analysis of 225 comments posted in the CEVF. The study was conducted between May and December 2008. Results The average score for observance of the CE by the respondents themselves was high (over 4/5), between 3.5-4/5 for the observance by their colleagues and close to 3/5 for the CIH management. These results do not change when we compare by gender, age group and professional discipline. The comments on the values are information-rich, they mirror the ethical environment of the institution and show various ethical dilemmas and suggestions. Conclusions Results show that it is feasible for a publicly funded health care organization to develop a CE with the participation of employees and the support of the management. Results underscore the relevance of this strategy for the implementation, improvement and update of the CE as a responsibility shared by all workers. Practices consistent with ethical values are rewarded by social approval, enhance employee's confidence and coherence in decision-making and improve public engagement and institutional policies.